The mirror of science - Biernacki, Marek; Smoluk, Antoni (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
Mathematics is a family of theories; there is an interpretation of every science of the physical world in the corresponding mathematical structure. Hence, mathematics is the mirror of science in its entirety
Mathematical Economics, 2018, Nr 14 (21), s. 5-18
Keywords: mathematics; science; faith